Preparation of Porous Chitosan-Siloxane Hybrids Coated with Hydroxyapatite Particles - Shirosaki, Yuki (Biomed Res Int, 2015)
This paper describes the apatite deposition of chitosan-silicate porous hybrids derived from chitosan and γ-glycidoxypropyltrimethoxysilane (GPTMS) in alkaline phosphate solution. The preparation of porous hybrids with needle-like apatite on their surfaces is described. Following apatite deposition the porous hybrids maintained high porosity. The enzymatic degradation rate was low even after 6 months and the porous hybrids were very flexible and cut easily using surgical scissors.